Environmental inequality and economic valuation - Jasper N. Meya (University of Oldenburg, Department of Economics, 2018)
I study how the distribution of environmental goods and income affect the economic valuation of local public goods. I find that how environmental inequality affects societal willingness to pay (WTP) for environmental local public goods is determined by their substitutability as well as by how their provision is correlated with income. Specifically, environmental inequality decreases societal (WTP) for substitutes, but this effect is reversed if environmental goods are complements or distributed strongly in favour of richer households. Moreover, I show that sorting of richer households into places where environmental good endowment is high increases (decreases) societal WTP if and only if it is a substitute for (complement to) consumption goods. I propose novel adjustment factors for structural benefit transfer to control for differences in the spatial distribution of environmental local public goods. Using forest preservation in Poland as an empirical example, I find that societal WTP is up to 4 percent higher for equal access to forests and up to 8 percent higher for an equal distribution of both income and access to forests.
Keywords: D63; Q51; 330; inequality; environmental valuation; WTP; local public good; spatial distribution; benefit transfer; forest ecosystem services